IDENTIFIKASI SPESIES PLASMODIUM MALARIA DI DESA TEMUNIH KECAMATAN KUSAN HULU KABUPATEN TANAH BUMBU PROPINSI KALIMANTAN SELATAN - Nita Rahayu; Sri Sulasmi; Yuniarti Suryatinah (Balai Penelitian dan Pengembangan Kesehatan Baturaja, 2017)
Abstract. Malaria remain as health problem in the world with annual mortality number around 1 million. Either with Temunih Village (Tanah Bumbu District-South Kalimantan) which is still become malarian endemic area in Indonesia. Mix malaria infection (falciparum and vivax) was dominant in this village. We have done descriptive study using cross-sectional design to know which malarian plasmodium species that was dominant infecting people in Temunih Village. Our result showed that among 146 individuals examined by active case detection, mix malaria infection (falciparum and vivax) was dominant in older man with age 11-20 year (60% cases), while falciparum malaria was dominant in older woman with age 21-30 year (60% cases). On a contrary, we only found 1 case of vivax malaria in woman with age 11-20 year. It is suggested that people of Temunih Village should use Impregnated Bed Net when sleeping in the night and using repellant to avoid anopheles mosquito biting. Moreover, it is better for them to consume prophylaxis drug before going to work in the field or forest. Keywords:Malaria falciparum, Plasmodium vivax, Plasmodium falciparum